(untitled) (Journal of the College of Languages (JCL), 2023)
This article deals with the Arab-Islamic influence on the Argentine writer Luis Jorge Borges who is considered one of the greatest writers of the twentieth century. He speaks many languages and has a very significant cultural background. He is known for his great love of the Arabic language and his deep knowledge of oriental culture. Islamic and Arabic themes have always been present in his literary works and his writing style, whether in a novel, essay, or poetry. This descriptive study tries to study how the author uses Arabic material to express other ideas in an international literary style through quotes or metaphors. The article shows a small part of this Arab- Islamic influence by analyzing the poem entitled “Metaphors in the Thousand Nights and a Night” by the Argentine writer Luis Borges. Jorge Luis Borges es un escritor argentino considerado como uno de los mayores exponentes de la literatura del siglo XX políglota y poseedor de una cultura muy amplia, conocido por su gran amor por lo árabe y su profundo conocimiento de la cultura oriental. Los temas islámicos y árabes siempre han estado presentes en sus obras literarias y en el estilo de su escritura, ya sea narrada en novela, ensayo o poesía. En este estudio descriptivo intentamos estudiar cómo el autor empleó el material árabe para expresar sus ideas filosóficas en estilo o técnica literaria universal a través de las palabras adaptadas o las metáforas. El objetivo del artículo es mostrar la influencia árabe-islámica en la poesía del autor argentino Luis Borges mediante el análisis de su poema Metáfora en las Mil y Una Noches.